Genetic parameters and breeding strategies to enhance yield in local sweet potato (Ipomoea batatas (L.) Lam.) germplasm from southeast Sulawesi - Boer, Dirvamena; Muzuni, Muzuni; Warhamni, Warhamni (Jurnal AGRO, 2025)
Sweet potato (Ipomoea batatas (L.) Lam.) is an important food crop with strategic value for food security, dietary diversification, and the sustainability of rural livelihoods in Indonesia. Local sweet potato germplasm from Southeast Sulawesi represents a valuable genetic resource for breeding high-yielding and stress-resilient varieties. This study aimed to evaluate genetic diversity, heritability, trait correlations, and the direct and indirect contributions of agronomic traits to yield in 20 local sweet potato clones originating from Southeast Sulawesi. The experiment utilized a Randomized Complete Block Design (RCBD) with three replications, measuring 14 agronomic and physiological traits. The study was conducted under lowland tropical humid agroecosystem conditions in the Kendari area. Data were analyzed using analysis of variance, broad-sense heritability estimation, Pearson correlation, stepwise regression, and path analysis. Significant genetic variation was observed for all evaluated traits, with heritability values ranging from 58.43% to 97.08%. Tuber weight and tuber number per plant were identified as the primary yield determinants, whereas internode length exhibited a significant negative effect. Stepwise regression and path analysis confirmed that tuber weight had the strongest direct effect on yield, followed by tuber number. The integrative analytical approach applied in this study provides a comprehensive understanding of causal relationships among agronomic traits. These findings indicate that selection based on tuber weight and number of tubers per plant, combined with regulation of excessive vegetative growth, may enhance yield efficiency and support the development of high-yielding, locally adapted sweet potato varieties for tropical agroecosystems. ABSTRAK Ubi jalar (Ipomoea batatas (L.) Lam.) merupakan tanaman pangan penting yang memiliki nilai strategis dalam mendukung ketahanan pangan, diversifikasi konsumsi, dan keberlanjutan mata pencaharian masyarakat pedesaan di Indonesia. Plasma nutfah lokal ubi jalar dari Sulawesi Tenggara merupakan sumber daya genetik yang berharga untuk pemuliaan varietas berdaya hasil tinggi dan toleran terhadap cekaman. Penelitian ini bertujuan untuk mengevaluasi keragaman genetik, heritabilitas, korelasi antarkarakter, serta kontribusi langsung dan tidak langsung sifat agronomi terhadap hasil pada 20 klon ubi jalar lokal asal Sulawesi Tenggara. Percobaan disusun menggunakan Rancangan Acak Kelompok Lengkap dengan tiga ulangan, dan sebanyak 14 karakter agronomi dan fisiologis diamati. Penelitian dilaksanakan pada kondisi agroekosistem tropis lembap dataran rendah di wilayah Kendari. Data dianalisis menggunakan analisis ragam, estimasi heritabilitas arti luas, korelasi Pearson, regresi stepwise, dan analisis lintasan. Hasil penelitian menunjukkan adanya keragaman genetik yang signifikan pada seluruh karakter yang diamati, dengan nilai heritabilitas berkisar antara 58,43% hingga 97,08%. Bobot umbi dan jumlah umbi per tanaman secara konsisten teridentifikasi sebagai penentu utama hasil, sedangkan panjang ruas menunjukkan pengaruh negatif yang nyata. Regresi stepwise dan analisis lintasan mengonfirmasi bahwa bobot umbi memiliki pengaruh langsung terbesar terhadap hasil, diikuti oleh jumlah umbi per tanaman. Pendekatan analisis integratif ini memberikan pemahaman komprehensif mengenai hubungan kausal antar karakter. Temuan ini mengindikasikan bahwa seleksi berbasis bobot umbi dan jumlah umbi per tanaman, disertai pengendalian pertumbuhan vegetatif yang berlebihan, berpotensi meningkatkan efisiensi hasil serta mendukung pengembangan varietas ubi jalar unggul yang adaptif terhadap agroekosistem tropis.